2022
DOI: 10.1108/bl-11-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of gender differences via TAM in e-recruitment adoption in India: a multi-group analysis using MICOM

Abstract: Purpose This paper aims to answer two research questions: first, to study the factors that directly and indirectly influence the intentions of job-seekers and second, to examine the moderating role of gender differences in e-recruitment adoption through the application of technology acceptance model (TAM) in India. Design/methodology/approach A convenience sampling technique was used to collect online data via GoogleDocs through various online channels such as social media, LinkedIn and email. The final data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…Learned lessons: According to Kaur and Kaur (2022), developers and recruiters must provide meaningful information related to salary, location and job profile in e-recruitment to increase the adoption rate of tools such as online recruiting. In addition, system developers should encourage greater usability (considering gender characteristics and preferences) because users prefer them when they are easier to use and operate.…”
Section: The Role Of Technology and Web-based Information In Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Learned lessons: According to Kaur and Kaur (2022), developers and recruiters must provide meaningful information related to salary, location and job profile in e-recruitment to increase the adoption rate of tools such as online recruiting. In addition, system developers should encourage greater usability (considering gender characteristics and preferences) because users prefer them when they are easier to use and operate.…”
Section: The Role Of Technology and Web-based Information In Managementmentioning
confidence: 99%
“…In the fifth paper, Kaur and Kaur (2022) examine factors influencing job-seeker’s intentions and the moderating role of gender differences in e-recruitment adoption through the application of the technology acceptance model in India. Based on data collected through various online channels such as social networks, LinkedIn, and email from 364 final-year students, the results indicated that perceived usefulness (PU) and perceived ease of use (PEOU) had a direct impact on attitude (AT).…”
Section: The Role Of Technology and Web-based Information In Managementmentioning
confidence: 99%
“…According to the available literature, males are more susceptible to utility and expected performance because they are more task-oriented ( Assaker, 2020 ; Pal and Patra, 2021 ; Kaur and Kaur, 2022 ). In particular, Kaur and Kaur (2022) found that the correlation between PU and CI is stronger for males than for females, which suggests that gender moderates the relationship. We anticipate that the relationship between PU and CI will be stronger for males in the context of online learning.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The international literature widely recognises that HC, structural capital and relational capital are the elements that make up intellectual capital (IC) – which is considered the main asset responsible for improving performance, competitiveness, innovation capacity and boosting the generation of value and sustainability of organisations (see Jordão and Novas, 2017; Xiao et al , 2017; Agostini et al , 2020; Jordão et al , 2022). Furthermore, the literature (e.g., Calabrò et al , 2020; Matos et al , 2020; Kaur and Kaur, 2022) also suggests that HC is the core element of IC and, therefore, the basis for permanent improvements not only at the organisational level but also bringing benefits in economic and social terms.…”
Section: Introductionmentioning
confidence: 99%